Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.3109/14767058.2011.600796
|View full text |Cite
|
Sign up to set email alerts
|

Implications of maternal systemic oxidative stress in normal pregnancy and in pregnancy complicated by preeclampsia

Abstract: Oxidative stress in preeclampsia is the result of the increase in reactive oxygen species and of the decrease in antioxidants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Two hypotheses can be invoked to explain these findings. First, a higher plasma sST2 concentration may be a consequence of an intravascular inflammatory response which is exacerbated in preeclampsia when compared to an uncomplicated pregnancy [23,25,[168][169][170]. Indeed, it has been demonstrated that pro-inflammatory cytokines are increased in the plasma or serum of women with early-onset preeclampsia [35,41,42] and severe preeclampsia [36,40,41] when compared to women with uncomplicated pregnancies.…”
Section: Plasma Concentrations Of Soluble St2 Is Elevated In Preeclammentioning
confidence: 99%
“…Two hypotheses can be invoked to explain these findings. First, a higher plasma sST2 concentration may be a consequence of an intravascular inflammatory response which is exacerbated in preeclampsia when compared to an uncomplicated pregnancy [23,25,[168][169][170]. Indeed, it has been demonstrated that pro-inflammatory cytokines are increased in the plasma or serum of women with early-onset preeclampsia [35,41,42] and severe preeclampsia [36,40,41] when compared to women with uncomplicated pregnancies.…”
Section: Plasma Concentrations Of Soluble St2 Is Elevated In Preeclammentioning
confidence: 99%
“…A study performed by McCormick et al supported the finding that an increase in the permeability of capillaries may cause vasogenic edema and cortical blindness as a result (17). Complement activation and leucocyte aggregation lead to the formation of emboli in the retinal arterioles and manifest as Purtscher retinopathy (18).…”
Section: Pathophysiologymentioning
confidence: 94%
“…These immune cells, released upon placental ischemia can generate superoxide within the maternal vascular endothelium 7 . Indeed increased levels of ROS and 8-isoPGF2α, the free form of isoprostane, are found in placentas and in the circulation of women with preeclampsia 8, 9 , indicating that preeclampsia is accompanied by an increase in pro-oxidant factors. During hypertensive disorders peroxynitrite concentrations 10, 11 and ROS are also released by the maternal vascular endothelium and smooth muscle cells (SMC) stimulated by stress or angiotensin II.…”
Section: Introductionmentioning
confidence: 99%